Synthesis of Polystyrene Sulfonate and Its Characterization as a Polymer Electrolyte Membrane - Emil Salim; Afrizal Afrizal; Zilfadli Zilfadli (Akta Kimia Indonesia, 2021)
This study aims to synthesize polystyrene sulfonate (PSS) from polystyrene (PS) isolated from waste styrofoam. Sulfonation reaction of polystyrene was conducted using acetyl sulfonate as sulfonating agents with variation times and temperatures. The sulfonated products were characterized using FT-IR spectrophotometer, degree of sulfonation, cation exchange capacity, water uptake and thermal stability. The FTIR spectrums show vibration of O-H streching at wave number 3300-3400 cm-1, S=O streching at the wave number 1050-1200 cm-1 which indicates the presence of sulfonate groups. Sulfonation reaction at 40oC for 2 hours (SPS-40-2) gives the highest degree of sulfonation, cation exchange capacity, water uptake with values 1,960%, 0.1880 meq/gr, 9.04% respectively. Thermal gravimetry analysis shows that polystyrene sulfonate has better thermal stability than polystyrene.